Participatory local regulations based on local wisdom: study of local regulation formation policy of Kutai Kartanegara regency - Yulianingrum, Aullia Vivi; Nur, Insan Tajali; Prasetyo, Bayu; Aidil, Aidil; Haya, Dita Alika Fadia; Paturu, Reni Oktaviani (Trigin Publisher, 2023)
This study aims to determine the local government policy of Kutai Kartanegara Regency in arranging participatory local regulations to accommodate the local wisdom of Kutai Kartanegara society in the era of regional autonomy. It also analyzes the implementation of local wisdom regulation to ensure the existence of society. The methodology used is empirical juridical, where researchers use data collection techniques through interviews with the Legal Section of the Regional Government of Kutai Kartanegara Province. The method of data analysis is qualitative and deductive inference, that is, drawing conclusions from a general form to a specific form. The formation of participatory local regulations based on local wisdom becomes urgent when the implementation of regional autonomy is faced with global demands where people must follow technological developments. This can change the cultural values that have been developed in local communities, and the government is obliged to provide legal protection in the form of the formation of local regulations that contain local wisdom values and guarantee their sustainability.